(untitled) (Communication & Society, 2014)
Around 1950 there was an intense debate about U.S. aid to Francoist Spain. American magazines such as Look and Life devoted attention to the Spanish issue, and used photo essays to visually argue their positions. This article seeks to examine how this controversy was created through these photo essays that appeared in American magazines, the reaction of the Spanish public, and the response to American critics by magazines such as Mundo Hispánico and Semana. These cases demonstrate how part of the debate was also an image campaign structured around photo essays published in said illustrated magazines.